Entrepreneurial Culture and Financial Education Between Students of the Veracruzana University, Veracruz Region - Betancourt, Ignacio Ortiz (European Journal of Social Science Education and Research, 2019)
Entrepreneurial culture and financial education stand out as two fundamental issues on the international agenda, since these elements are considered in favor of the efficient use of financial resources, as well as the identification of opportunities for the development of self-employment projects, contributing to local economic growth.According to the National Commission for the Protection and Defense of Financial Services Users (CONDUSEF, 2012), financial education can be defined as the set of actions that imply learning to manage money better, being foresighted, consuming in a rational way, And learn to invest, know how to take care of your assets and use financial products and services with responsibility.Similarly, Smyth (2011) points out that financial education is the process by which consumers improve the understanding of financial products and acquire a greater understanding of financial risks and market opportunities, by making economic decisions with Information. In addition, he points out that an important part of our decisions is associated with financial behavior, which directly impacts his personal and family environment, from the search for funding for studies to planning for retirement. Thus, having an adequate financial education will favor an intelligent selection of financial products, based on well-informed decisions.